(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the scientific views of Eastern thinkers on the problems of adolescence and deviant behavior. In the teachings of thinkers, the educational activities of the family and parents are recognized as one of the main factors in the comprehensive development of the child. In their opinion, the spiritual and moral environment in the family directly affects the formation of the child’s personality, behavior and social relations.